2016
DOI: 10.3350/cmh.2016.22.1.160
|View full text |Cite
|
Sign up to set email alerts
|

Survival outcomes of hepatic resection compared with transarterial chemoembolization or sorafenib for hepatocellular carcinoma with portal vein tumor thrombosis

Abstract: Background/Aims:Treating hepatocellular carcinoma (HCC) with portal vein tumor thrombosis (PVTT) remains controversial. We compared the outcomes of hepatic resection (HR), transarterial chemoembolization (TACE), and sorafenib therapy as treatments for HCC with PVTT.Methods:Patients diagnosed as HCC with PVTT between January 2000 and December 2011 who received treatment with sorafenib, HR, or TACE were included. Patients with main PVTT, superior mesenteric vein tumor thrombosis, or Child-Turcotte-Pugh (CTP) cla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
114
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(117 citation statements)
references
References 18 publications
3
114
0
Order By: Relevance
“…The details and reasons for exclusion requiring consensus between the authors are described in http://onlinelibrary.wiley.com/doi/10.1002/hep.29883/suppinfo. Finally, 18 studies reporting PH versus TACE in BCLC stage B or stage C patients were included in the systematic review and meta‐analysis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The details and reasons for exclusion requiring consensus between the authors are described in http://onlinelibrary.wiley.com/doi/10.1002/hep.29883/suppinfo. Finally, 18 studies reporting PH versus TACE in BCLC stage B or stage C patients were included in the systematic review and meta‐analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Eighteen trials (one RCT, five PSM NRCTs, and 12 NRCTs) consisting of 20 data sets and a total of 5,986 patients were included in the meta‐analysis. The RCT was a single‐center trial conducted in China .…”
Section: Resultsmentioning
confidence: 99%
“…A median OS period after treatment with TACE was reported to be 5.6-16.5 mo in patients with HCC accompanied by PVTT[11-13]. A median OS period after treatment with surgery was reported to be 6-19.9 mo[14-16]. Furthermore, Minagawa et al[16] reported a high survival rate in these patients with the combination of TACE followed by hepatic resection.…”
Section: Discussionmentioning
confidence: 99%
“…Surgery has been considered contraindicated by many institutions, including the BCLC system [41] . However, many studies, particularly those from the Asian centers, have reported hepatic resection to be safe and effective for patients with portal vein invasion [28,[42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58] [ Table 3]. The median 1-, 3-and 5-year overall survival rates for patients with all forms of portal vein invasion treated with surgery were 61.0%, 32.9% and 27.0% respectively.…”
Section: Surgerymentioning
confidence: 99%
“…[48] Vp1 Lee et al . [47] Vp1 In view of this, much effort has been made to devise new intra-arterial therapies with less systemic toxicities. In recent years, TARE has become an alternative to TACE in treating high-burden HCC.…”
Section: Transarterial Radioembolizationmentioning
confidence: 99%